Salvia miltiorrhiza in Treating Cardiovascular Diseases: A Review on Its Pharmacological and Clinical Applications - Ren, Jie; Fu, Li; Nile, Shivraj Hariram; Zhang, Jun; Kai, Guoyin (Frontiers in Pharmacology, 2019)
Bioactive chemical constitutes from the root of Salvia miltiorrhiza classified in two major groups, viz; liposoluble tanshinones and water-soluble phenolics. Tanshinone IIA is a major lipid soluble compound having promising health benefits. The in vivo and in vitro studies showed that the tanshinone IIA and salvianolate have a wide range of cardiovascular and other pharmacological effects, including antioxidative, anti-inflammatory, endothelial protective, myocardial protective, anticoagulation, vasodilation, and anti-atherosclerosis, as well as significantly help to reduce proliferation and migration of vascular smooth muscle cells. In addition, some of the clinical studies reported that the S. miltiorrhiza preparations in combination with Western medicine were more effective for treatment of various cardiovascular diseases including angina pectoris, myocardial infarction, hypertension, hyperlipidemia, and pulmonary heart diseases. In this review we demonstrated the potential applications of S. miltiorrhiza, including pharmacological effects of salvianolate, tanshinone IIA and its water-soluble derivative like sodium tanshinone IIA sulfonate, moreover we also provided details about the clinical applications of S. miltiorrhiza preparations in controlling the cardiovascular diseases.